2020
DOI: 10.1161/jaha.119.014578
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Dynamics Is Altered in Young Adults With Cryptogenic Ischemic Stroke: A Case‐Control Study Utilizing Advanced Echocardiography

Abstract: Background Ischemic stroke in young individuals often remains cryptogenic. Some of these strokes likely originate from the heart, and atrial fibrosis might be one of the etiological mechanisms. In this pilot study, we investigated whether advanced echocardiography findings of the left atrium ( LA ) of young cryptogenic stroke patients differ from those of stroke‐free controls. Methods and Results We recruited 30 cryptogenic ischemic stroke pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
2
16
1
Order By: Relevance
“…Our findings should be contrasted to other studies, which found that cryptogenic stroke was similar to CE stroke, most notably when using profiles of differentially expressed genes 14 . In addition, Embolic Stroke of Undetermined Source (ESUS) is being increasingly recognized as an important subset of cryptogenic stroke 8 , 15 , 16 . While our study did not find many cryptogenic strokes that fit the cardiac phenotype, 93 (78.8%) of cryptogenic strokes in our cohort with sufficient work-up met the criteria for ESUS 17 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings should be contrasted to other studies, which found that cryptogenic stroke was similar to CE stroke, most notably when using profiles of differentially expressed genes 14 . In addition, Embolic Stroke of Undetermined Source (ESUS) is being increasingly recognized as an important subset of cryptogenic stroke 8 , 15 , 16 . While our study did not find many cryptogenic strokes that fit the cardiac phenotype, 93 (78.8%) of cryptogenic strokes in our cohort with sufficient work-up met the criteria for ESUS 17 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Detailed baseline data and clinical data and basic left ventricular (LV) measurements have been published earlier (Pirinen et al 2020). Compared with controls, patients were heavier, had a larger waist circumference, higher body-mass index (BMI) and a larger BSA.…”
Section: Study Populationmentioning
confidence: 99%
“…Characteristics of study subjects have been previously published. 6 15 16 None of the patients had PFO closure prior to CMR.…”
Section: Methodsmentioning
confidence: 98%
“…Recent studies suggest that left atrial (LA) dynamics are altered in cryptogenic stroke. 6 7 Atrial fibrosis and atrial cardiomyopathy have been suggested as possible mechanisms, 8 9 but also PFO with atrial septal aneurysm has been associated with LA dysfunction, suggested to be an additional contributing factor to the mechanism of PFO-related stroke. 10 However, there has been only a little interest on the right atrium (RA) in patients who had a stroke.…”
Section: Introductionmentioning
confidence: 99%